Behavioral Economics and Islamic Financial Consumer Protection in ASEAN: A Conceptual Framework - Muhfiatun (Al-Mashrof: Islamic Banking and Finance, 2026)
Islamic financial consumers increasingly encounter complex contracts, digital interfaces, personalized marketing, and cross-channel fraud risks. Conventional consumer protection, which relies mainly on disclosure and formal compliance, may be ineffective when decisions are shaped by bounded rationality, limited attention, present bias, overconfidence, framing, and social influence. This study develops an integrative conceptual framework for consumer protection in selected ASEAN jurisdictions, focusing on Indonesia, Malaysia, Singapore, and Brunei Darussalam. A structured integrative review synthesizes peer-reviewed literature, international standards, and current regulatory documents concerning behavioral economics, Islamic finance, digital finance, and market conduct. The analysis identifies four complementary protection mechanisms: regulatory protection, behavioral protection, digital protection, and Sharia governance. These mechanisms are proposed to strengthen consumer capability and produce calibrated institutional, technological, and Sharia trust. The framework further links calibrated trust to decision quality, reduced exposure to mis-selling and fraud, effective redress, consumer welfare, and responsible financial inclusion. The study contributes by explicitly incorporating behavioral and digital vulnerabilities into Islamic financial consumer protection and by formulating seven propositions for future empirical testing. Policy implications include plain-language disclosure, suitability-by-design, dark-pattern and sludge audits, secure complaint channels, and verifiable Sharia assurance. Keywords: behavioral economics; consumer protection; Islamic finance; digital finance; ASEAN